STUDY ON COD-ESTIMATION IN RIVER AND WASTE WATER BY PORTABLE ULTRAVIOLET ABSORBANCE PHOTOMETR - KATO, Susumu; SATO, Kunihiko; TAKAHASHI, Masaaki; SHIMONO, Masayuki (Journal of Environmental Conservation Engineering, 2003)
A simple, inexpensive and portable ultraviolet absorbance photometer was developed for COD estimation not only for river water but also for waste water. The performance of this instrument such as Zero-drift, 100%-drift were very good. Moreover good liner response with slope 1 was obtained between standard solution (potassium hydrogen phthalete) and absorbance at ultraviolet 254 nm. Using filtered various testing solutions with 0.45μm pore size (river water, leachate, food industry, animal farm and septic tank), we compared the absorbance from this instrument with conventional spectrophotometer. Finally, good linear relationship: UV254 (this instrument) =0.98×UV254 (spectrophotometer) -0.004 (R=0.99) was obtained. For the samples collected in the Japan, COD-Mn was estimated by following equation: COD-Mn (mg/l) =60×UV254+1.3, and for samples collected in Japan, the Philippines and Thailand, COD-Cr (mg/l) =169×UV254. However, poor results were obtained from testing solutions which contained high concentration of SS (>30mg/l ), colored or fluorescent brightening agent. Although, the weak points for these samples were overcome by a simple operation, such as dilution.